Adenoma Detection Rates Decline with Increasing Procedural Hours in an Endoscopist’s Workload - Majid A Almadi; Maida Sewitch; Alan N Barkun; Myriam Martel; Lawrence Joseph (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Operator fatigue may negatively influence adenoma detection (AD) during screening colonoscopy.